2007
DOI: 10.1007/s00467-006-0316-y
|View full text |Cite
|
Sign up to set email alerts
|

Triggers of relapse in steroid-dependent and frequently relapsing nephrotic syndrome

Abstract: An awareness of the triggers of relapse is critical for the control of steroid-dependent, frequently relapsing nephrotic syndrome (SDFRNS). We have investigated the triggers, usually described as 'episodes', to such relapses within a temporal context. Thirty-five patients with SDFRNS were analyzed retrospectively. A total of 442 relapses occurred in 2499 patient-months. The relapses were classified into two groups: those with episodes (E+) and those without episodes (E-). There were 135 E+ relapses and 296 E- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 11 publications
(11 reference statements)
6
34
0
Order By: Relevance
“…Related pharmacological studies have shown that trametes robiniophila murr, being rich in polysaccharides, is a biological response modifier and can stimulate many elements of the immune system to enhance immunity. Clinical studies have shown that it has certain effects on children with recurrent respiratory tract infections [3,4], which is one cause of relapse in children with primary nephrotic syndrome [5,6]. Therefore, in the present study, ADR rat models were selected to observe the effects of HQH on experimental renal disease and to explore its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Related pharmacological studies have shown that trametes robiniophila murr, being rich in polysaccharides, is a biological response modifier and can stimulate many elements of the immune system to enhance immunity. Clinical studies have shown that it has certain effects on children with recurrent respiratory tract infections [3,4], which is one cause of relapse in children with primary nephrotic syndrome [5,6]. Therefore, in the present study, ADR rat models were selected to observe the effects of HQH on experimental renal disease and to explore its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…However, about 70% of the children experience relapsing course in the next 12 months nontreatment period 3 . The relapses are often precipitated by infections 6,9,14 which become troublesome for the patients as well as parents. Certain factors such as age, gender, time to response, duration of treatment of initial episode and frequency of relapses in the initial six months have been found to predict the relapses in these patients 1,10,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A study on the epidemiology of renal failure (RF) expressed high incidence of RF at PUHC-CDG of Ouagadougou (13). Takahashi et al, conducted a study on relapse triggers in children with steroid dependency; they observed 442 relapses in 2499 patients (14). Yousefichaijan et al, observed no statistically significant correlation between children with attention deficit hyperactivity disorder (ADHD) and steroiddependent nephrotic syndrome (SDNS), and their healthy counterparts (15), which was not investigated in the current study.…”
Section: Discussionmentioning
confidence: 53%